THE CORRELATION BETWEEN CONDITIONAL CASH TRANSFER AND FINANCIAL INCLUSION: A CASE STUDY OF THE 2016 AND 2022 NATIONAL SOCIOECONOMIC SURVEYS - Tri Dara Marhamah; Irfani Fithria Ummul Muzayanah (RADJA PUBLIKA, 2025)
The distribution of conditional cash transfer plays a crucial role in increasing financial inclusion. When households receive cash transfer, they can expand their use of financial services, such as savings, credit, and other financial services. The mechanism for distributing conditional cash transfer is a concern, given that recipients are low-income individuals who are excluded from the formal financial system. The purpose of this thesis is to examine the relationship between conditional cash transfer from the Program Keluarga Harapan (PKH), distributed non-cash through the Family Welfare Card, and financial inclusion, measured by three levels of banking system utilization: no financial inclusion, low financial inclusion, and high financial inclusion, based on savings account ownership and access to credit. The study considers individual economic characteristics, individual characteristics, and regional characteristics. This study analyzes cross-sectional data from The Statistics Indonesia in 2016 and 2022 using marginal effects from probit regression. The results show that households receiving PKH cash transfer through the Family Welfare Card tend to have access to financial inclusion, both in the form of savings account ownership and access to credit. This indicates that the cashless distribution of PKH through the Prosperous Family Card has positive implications and acts as an effective catalyst in increasing the financial inclusion of household heads. The driving factor, namely, poor and educated households, indicates a higher probability of accessing financial inclusion.